Pengaruh Kemampuan Pembelajaran Organisasional Terhadap Kompetensi Inti Organisasi, dan Kinerja Organisasi Perguruan Tinggi Swasta di Propinsi NTT Suatu Tinjauan Literatur Untuk Membangun Hipotesis Penelitian - Rafael Octavianus Byre (FAKULTAS EKONOMI UNIVERSITAS FLORES, 2020)
Empirically, this paper is expected to see the extent of the development of organizational learning models in the Development of Private Higher Education in the Province of East Nusa Tenggara Province by including the dimensions of the organization's core competencies, and organizational performance in previous strategy research. With the stages of model development which can be seen the contribution and contribution of each previous research to the research carried out mainly in building research hypotheses. In this paper we also want to look gradually at how to understand the partial effect of organizational learning on the organization's core competencies, on diversification strategies and organizational performance. And how all the aspects examined above contribute to further studies in the field of strategy management concerning the effect of organizational learning on core competencies, diversification strategies and organizational performance. The design of this research is mostly done on companies in the field of services in general and some research on higher education organizations. Looking at / reviewing all the studies that have been done by previous researchers whose variables are used as the basis for building and developing hypotheses in this paper, namely, the influence between organizational learning, organizational core competencies and performance. With the following stages begin with searching, separating articles, extracting data, synthesizing data, reporting data. The main contribution in this research is to illustrate that how the construct of organizational learning needs to be developed in improving the organization's core competencies, which in the end is expected to improve the performance of private higher education organizations in NTT Province.